Implementation of On Page SEO for Gogalas Website - Sulistianingsih, Indri; Akbar, Ahmad; Sari, Nova Maya; Rahma, Astri Mutia (International Conference on Sciences Development and Technology, 2022)
The study investigates various fundamental elements of On-Page SEO, encompassing the optimization of titles, the quality of content, the structure of meta descriptions and URLs, the speed of web pages, the establishment of trustworthiness, and the implementation of internal linking. The study endeavors to showcase the collective impact of these strategies on enhancing one's online profile through careful analysis and application. The implementation phase encompasses the strategic incorporation of pertinent keywords in titles and content, the optimization of meta descriptions to improve click-through rates, and the structuring of URLs for the purposes of clarity and user-friendliness. The study also examines the significance of page loading speed and security measures, both of which have pivotal roles in enhancing user experience and search engine results. Moreover, the study highlights the significance of internal linking in promoting smooth navigation and improving the overall structural coherence of the website. The study offers practical insights for website owners, digital marketers, and SEO practitioners that aim to optimize their online platforms by demonstrating the sequential adoption of various approaches. This study ultimately illustrates the efficacy of implementing On-Page SEO tactics in enhancing search engine visibility, augmenting organic traffic, and providing a more gratifying user experience for the